ADORASI EKARISTI SEBAGAI STRATEGI REFORMASI IMAN KAUM MUDA - Emiliana Vivi (Lembaga Penelitian STKIP Widya Yuwana, 2026)
In the Catholic tradition, the Eucharist occupies a central place as the source and summit of Christian life. It is one of the devotional practice rooted in the real presence of Christ in the Eucharist. In the contemporary context, young people face various challenges, including digital distraction, rapid cultural change, and an ongoing search for meaning. This phenomenom call for forms of faith experience that are reflective and transformative. This article aims to examine Eucharistic Adoration as a means of faith reform for young people within the life of the Church. This study employs a qualitative library research method by analyzing theological books, official Church documents, and scholarly journal articles related to Eucharistic spirituality and youth faith. Data analysis is conducted by adapting the Miles and Huberman model, which includes data collection, data reduction, data examination, and conclusion drawing. The findings indicate that Eucharistic Adoration provides a contemplative spiritual space that enables young people to encounter Christ personally, reflect on their life experiences, and integrate faith with everyday realities. Therefore, Eucharistic Adoration can be understood as a theologically relevant and meaningful practice for fostering faith reform among the young people, especially when the are accompanied by contextual pastoral guidance.